Indicators of the application of public relations theories in government institutions (Survey Study in Misan Governorate) - Leith Sabbar Jaber, Dr. (lark, 2023)
This research attempts to demonstrate the importance of applying theoretical indicators of public relations in government institutions and to identify the type of those indicators in terms of application and practice, as well as to identify the degree of preference among public relations practitioners for theoretical indicators in government institutions. Maysan through its exposure to the opinions and visions of workers in its public relations departments, who numbered (40) respondents
Keywords: Indicators, Theory, Public Relations, Government Institutions